Comprehensiveness in child healthcare teaching in Undergraduate Nursing: perspective of teachers - Emília Gallindo Cursino; Elizabeth Fujimori; Maria Aparecida Munhoz Gaíva (SciELO, 2014)
This qualitative study analyzed, from the teacher's perspective, if the principle of comprehensiveness is included in child healthcare teaching in nursing education. The participants were 16 teachers involved in teaching child healthcare in eight undergraduate nursing programs. Data collection was performed through interviews that were submitted to thematic content analysis. The theory in teaching incorporates comprehensive care, as it is based on children's epidemiological profile, child healthcare policies and programs, and included interventions for the promotion/prevention/rehabilitation in primary health care, hospitals, daycare centers and preschools. The comprehensive conception of health-disease process allows for understanding the child within his/her family and community. However, a contradiction exists between what is proposed and what is practiced, because the teaching is fragmented, without any integration among disciplines, with theory dissociated from practice, and isolated practical teaching that compromises the incorporation of the principle of comprehensiveness in child healthcare teaching.